RESPONS PERTUMBUHAN BIBIT KAKAO (Theobroma cacao L.) TERHADAP BEBERAPA KOMPOSISI KOMPOS KULIT BUAH KAKAO DENGAN SUBSOIL ULTISOL DAN PUPUK DAUN - Henni Fiona Damanik; Jonis Ginting; Irsal Irsal (Universitas Sumatera Utara, 2013)
ABSTRACTThe response of cocoa seedlings growth (Theobroma cacao L.) by application some composition ofcocoa waste compost with subsoil ultisol and leaf fertilizer. The research was conducted incommunity land, Tanjung Selamat at analtitude ± 57 meters above sea level since May 2012 untilSeptember 2012 using Randomized Block Design (RDB) factorial with two factors. The first factoris Cocoa Waste Compost with Subsoil Ultisol (25 + 4975, 75 + 4925, 125 + 4875, 175 + 4825, 225+ 4775 g/polybag). The second factor is leaf fertilizer (1, 3, and 5 cc/liter). The Parameter observedincludes plant hight (cm), diameter of stem (mm), leaf area total (cm2), fresh and dry weight ofcrown (g) fresh and dry weight of root (g). The result of reseach showed that planting mediainfluential significantly on plant height and diameter of stem. Present of leaf fertilizer influentialsignificantly on diameter of stem and dry off root. Interaction between planting media present offertilizer not influential significantly on plant height, diameter of stem, total of broad leaf, fresh anddry weight of crown, fresh and dry off root.Key words : cocoa waste compost, leaf fertilizer, cacao, nursery